Effects of maternal and post-weaned rumen-protected folic acid supplementation on slaughter performance and meat quality in offspring lambs. Issue 8 (28th October 2021) - Li, H.Q.; Wang, B.; Li, Z.; Luo, H.L.; Zhang, C.; Jian, L.Y.; Gao, Y.F.; Lu, W.; Zhao, X.G.
Abstract: The present study was undertaken to evaluate the influence of rumen-protected folic acid (RPFA) on slaughter performance, visceral organ and gastrointestinal tract coefficients, and meat quality in lambs. Sixty-six lambs from 120 Hu ewes were selected based on body weight and maternal diets and then assigned to six groups using a randomised block experimental design in a 3 × 2 factorial arrangement. The first factor was folic acid (FA) as RPFA in the maternal diet (0 mg/kg (M0F), 16 mg/kg (M16F) or 32 mg/kg (M32F) on DM basis). The second factor was FA in the lambs' diet from weaning until slaughter (0 mg/kg (OC) or 4·0 mg/kg (OF)). The results indicated that the addition of 16 mg/kg FA to the maternal diet increased pre-slaughter weight (PSW), dressing and meat percentage, the reticulum and omasum coefficients, length of the jejunum and ileum, tail fat and perirenal fat coefficient and a * value of the meat colour. The addition of RPFA to the lambs' diet increased PSW, dressing and meat percentage, eye muscle area, abomasum weight, weight and length of the small intestine, but reduced the coefficients of tail fat. An M × O interaction was observed for the weights of heart, lungs, rumen and total stomach, weight and coefficient of omental fat and the girth rib value. Collectively, RPFA in the maternal and lambs' diet improved slaughter performance and meat quality by stimulating the morphological development of the gastrointestinal tract and the distribution of fat in the body.